EP732 Bladder endometriosis mimicking invasive pelvic malignancy. (1st November 2019) - Loh, M; Goh, C; Lim, Y
Abstract : Introduction/Background: Endometriosis, although common, rarely involves of the urinary tract, with bladder being the most commonly involved organ. First described in 1921 1, the pathogenesis, management, impact on fertility, and risk of malignant transformation of bladder endometriosis still remains controversial. Methodology: We report a case of a patient presenting with an infiltrative pelvic mass with local invasion into the bladder. Results: The patient, a 49 year old Chinese female with 2 previous cesarean sections and a laparoscopic myomectomy, had no history or symptoms suggestive of endometriosis (dysmenorrhea, dyschezia, dyspareunia, chronic pelvic pain). An enlarged left ovary was seen on ultrasound pelvis with an irregular papillary focal mucosal lesion in the left lateral wall of the bladder with bladder invasion. A magnetic resonance imaging (MRI) of the pelvis confirmed an invasive bladder lesion (figure 1). The 4 cm ovarian mass was inseparable from the left uterus. There were no enlarged pelvic lymph nodes or ascites. Ovarian tumour markers, renal function and an ultrasound of bilateral kidneys were normal. She underwent a total abdominal hysterectomy bilateral salpingectomy with bladder tumour excision and bilateral double J stent insertions. Intraoperatively, the solid left ovarian lesion noted on scan was found to be a 5 cm uterine fibroid. The 3 cm tumour involving the lower uterine segment and bladder extended into the bladder mucosa (figure 2). The tumour was removed en bloc with the uterus, with frozen section noting endometriosis. Both tubes and ovaries and intraperitoneal survey were normal with no pelvic endometriosis. Conclusion: Isolated urinary tract endometriosis is rare and may mimic malignancy. It is thus an important differential diagnosis to consider in a woman presenting with an infiltrative bladder mass. Management may be in the form of hormonal therapy or surgery, where complete excision of the bladder mass is ideal to minimize recurrence. Disclosure: Nothing to disclose.